Effectiveness of biofeedback therapy on low anterior resection syndrome: a systemic review with meta-analysis - Jing Zhang; Qin-Bing Zhu; Yu-Sha Zeng; Ya-Hong Xue (Frontiers in Medicine)
BackgroundAs a series of bothersome bowel dysfunction symptoms, low anterior resection syndrome (LARS) has a high incidence after rectal cancer surgery, which grievously impairs health-related quality of life. There have been an increasing number of studies on biofeedback therapy (BFT) to recover intestinal function in patients following anus-preserving surgery. However, few systematic reviews or meta-analyses have been reported.ObjectiveThe purpose of this systematic review with meta-analysis was to identify the short-term and long-term effects of BFT on subjective and objective indicators of LARS.MethodsRandomized controlled trials (RCT) published in PubMed, Cochrane Library, Web of Science, Embase, Chinese National Knowledge Infrastructure (CNKI), Wan Fang Data, China Biology Medicine disc (CBM), and Wei Pu (VIP) database from January 2012 to June 2024 were systematically searched. In accordance with PRISMA guidelines, the pooled findings were examined by Review Manager version 5.4.ResultsThe review finally included 14 RCT studies, with a total of 1,126 relevant patients. The meta-analysis results showed that following BFT, the mean resting pressure of the anal canal (MD = 5.53; 95% CI: 2.57, 8.49; Z = 3.66; p = 0.0003), the mean initial rectal sensation threshold (MD = 3.04; 95% CI: 1.84, 4.24; Z = 4.96; p < 0.00001), and the incidence rate of LARS (RR = 0.42; 95% CI: 0.31, 0.57; Z = 5.60; p < 0.00001) in the BFT intervention group were significantly better than those in the control group, However, there was no statistically significant differences in the Memorial Sloan-Kettering Cancer Center (MSKCC) intestinal function questionnaire score (MD = 0.79; 95% CI: −0.35, 1.93; Z = 1.37; p = 0.17), the CCIS (Wexner incontinence score) (MD = −0.67; 95% CI: −2.12, 0.78; Z = 0.91; p = 0.36), the LARS score (MD = −2.35; 95% CI: −6.07, 1.37; Z = 1.24; p = 0.22) and Xu ZF et al. “Five points Ten scores” excellent rate (RR = 4.59; 95% CI: 0.37, 56.35; Z = 1.19; p = 0.23) between the two groups.ConclusionOur systematic review and meta-analysis indicate that BFT may improve the mean resting pressure of the anal canal and the mean initial rectal sensation threshold, reducing the incidence rate of LARS. Still, high-quality studies are necessary to explore the BFT standard for LARS.Systematic review registrationPROSPERO: CRD42024519785, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024519785.